Making a Difference : 30 Years of TDR - Ridley, R. G.; Fletcher, E. R. (2012)
When the UNICEF/UNDP/World Bank/WHO Special Programme for Research and Training in Tropical Diseases (TDR) was established in the mid-1970s, it represented an innovative institutional formula in terms of its structure and the manner in which scientists were convened from both developed and developing countries to address some of the world's most neglected parasitic diseases. A review of TDR's historical record sheds light not only on some important milestones in tropical-disease research, but also on how future challenges could be approached and hopefully surmounted.